Predictors of Stress Level Toward COVID-19 Delta Variant Among Healthcare Workers - Asri Noor; Ermi Girsang; Ali Napiah Nasution; Tan Suyono; Putranto Manalu (Universitas Aisyah Pringsewu, 2023)
New variants have increased the number of COVID-19 patient cases again and impacted the mental health conditions of health workers on duty at the hospital. This study aims to analyze the relationship between risk factors such as age, gender, resilience, and self-efficacy with the level of stress experienced by health workers. This study used a cross-sectional design and was conducted in December 2021 involving 113 health workers of Royal Prima Medan Hospital. The Spearman Rank test was used to analyze the relationship between the predictors and the stress level of health workers (p= 0.05). The analysis showed that the majority of health workers experienced mild stress (67.30%). Rank Spearman test results showed that age (p=0.049; r=0.185), gender (p=0.016; r=0.227), resilience (p=0.000; r= -0.557), and self-efficacy (p=0.000; r=0.343) were significantly associated with the level of stress experienced by health workers. Management needs to pay attention to workload, a safe work environment, and provide training so that health workers can manage and minimize the risk of work stress while providing health services to COVID-19 patients.Abstrak: Kemunculan varian baru enyebabkan peningkatan kembali jumlah kasus pasien COVID-19 dan berdampak pada kondisi mental petugas kesehatan yang bertugas pada rumah sakit. Studi ini bertujuan untuk menganalisis hubungan faktor risiko seperti umur, jenis kelamin, resiliensi, dan self efficacy dengan tingkat stres yang dialami petugas. Studi ini menggunakan desain cross-sectional dan dilaksanakan pada bulan Desember 2021 dengan melibatkan sebanyak 113 tenaga kesehatan Rumah Sakit Royal Prima Medan. Uji Rank Spearman digunakan untuk menganalisis hubungan antara pediktor dengan tingkat stres tenaga kesehatan (p= 0,05). Dari hasil analisis menunjukkan mayoritas tenaga kesehatan mengalami stres ringan (67,30%). Hasil uji Rank Spearman menunjukkan bahwa usia (p=0,049; r=0,185), jenis kelamin (p=0,016; r=0,227), resiliensi (p=0,000; r= -0,557), dan self efficacy (p=0,000; r=0,343) berhubungan signifikan dengan tingkat stres yang dialami tenaga kesehatan. Pihak manajemen perlu memerhatikan beban kerja, lingkungan kerja yang aman, dan memberikan pelatihan agar petugas kesehatan mampu mengelola dan meminimalisir resiko stres kerja selama memberikan pelayanan kesehatan pada pasien COVID-19.